PERAN SISTEM PENGENDALIAN MANAJEMEN PADA PRESTASI KARYAWAN BERDASARKAN KINERJA KARYAWAN DI PT EXPLORINDO - Reinaldi Pangaribua; Muhammad Ardi Nupi Hasyim; Ega Nurmala Chaerudin; Karmila Putri Amin (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2020)
This study aims to examine the effect of management control systems, employee performance,on the performance of PT Explorindo employees engaged in services namely IT and telecommunicationslocated in South Jakarta. Testing this research on HRD. Based on the results of this study the authors found that the management control system, employee performance, and employee performance know the application of management control structures on employee performance in the company. This research uses descriptive analysis because the data used are questionnaires. The results of this study indicate that the effect of management control systems has a positive effect on employee performance in the company to improve employee performance.